An Event Related Field Study of Rapid Grammatical Plasticity in Adult Second-Language Learners - Bastarrika, Ainhoa; Davidson, Douglas J. (Frontiers in Human Neuroscience, 2017)
The present study used magnetoencephalography (MEG) to investigate how Spanish adult learners of Basque respond to morphosyntactic violations after a short period of training on a small fragment of Basque grammar. Participants (n=17) were exposed to violation and control phrases in three phases (pretest, training, generalization-test). In each phase participants listened to short Basque phrases and they judged whether they were correct or incorrect. During the pre-test and generalization-test, participants did not receive any feedback. During the training blocks feedback was provided after each response. We also ran two Spanish control blocks before and after training. We analyzed the event-related magnetic- field (ERF) recorded in response to a critical word during all three phases. In the pretest, classification was below chance and we found no electrophysiological differences between violation and control stimuli. Then participants were explicitly taught a Basque grammar rule. From the first training block participants were able to correctly classify control and violation stimuli and an evoked violation response was present. Although the timing of the electrophysiological responses matched participants’ L1 effect, the effect size was smaller for L2 and the topographical distribution differed from the L1. While the L1 effect was bilaterally distributed on the auditory sensors, the L2 effect was present at right frontal sensors. During training blocks two and three, the violation-control effect size increased and the topography evolved to a more L1-like pattern. Moreover, this pattern was maintained in the generalization test. We conclude that rapid changes in neuronal responses can be observed in adult learners of a simple morphosyntactic rule, and that native-like responses can be achieved at least in small fragments of second language.